Comparative evaluation of proteinase K and dithiothreitol as pretreatments for extracting nucleic acids from respiratory samples for multiplex PCR - Yanjun Chang; Ting Li; Yanfang Niu; Xiaodong Guan; Yarong Xie (BMC Microbiology)
Abstract Background Lower respiratory tract infections are frequently caused by bacteria, and the rapid identification of pathogens is crucial for guiding treatment. Multiplex PCR(M-PCR) can detect multiple pathogens simultaneously, but mucus and other cells in lower respiratory tract samples may interfere with nucleic acid detection. In this study, we compared the effectiveness of two pretreatment methods—proteinase K(PK) and dithiothreitol(DTT)—in detecting multiple pathogens using M-PCR in bronchoalveolar lavage fluid(BALF) and sputum samples. Methods A total of 30 BALF samples and 20 sputum samples were collected. These samples were pretreated with PK and DTT, respectively. Bacterial structural changes and background material were examined using Gram staining. Nucleic acid purity and concentration were assessed following extraction. Finally, the detection rate of several common pathogens associated with lower respiratory tract infections was analyzed using M-PCR. Results Gram staining indicated that both PK and DTT effectively destroyed the bacterial structure and reduced background material in BALF samples, while DTT was more effective samples compared to PK in sputum. The M-PCR results indicated no significant difference in Ct values for Streptococcus pneumoniae, Klebsiella pneumoniae, Haemophilus influenzae, and Pseudomonas aeruginosa between PK and DTT-treated BALF samples. The results of nucleic acid extraction showed no difference in purity and concentration of nucleic acids after treatment with PK and DTT in BALF and sputum samples. After PK treatment, the Ct values for the four bacteria in sputum samples were different from those in BALF samples treated with the three methods, while after DTT treatment, only K. pneumoniae and H. influenzae showed differences compared to BALF. There was no difference in bacterial detection rates between PK and DTT treatments of BALF, both of which were 100%. In sputum samples, the bacterial detection rate after DTT treatment was 100%, significantly higher than the 87.5% detection rate after PK treatment (P < 0.05). Conclusion PK and DTT exhibited similar pretreatment effects on BALF samples, with neither having an impact on the results. However, DTT was superior to PK in reducing interference and enhancing the sensitivity of M-PCR for bacterial detection in sputum samples, making it the preferred pretreatment for sputum.